The Effect of Cake Applications on English Learning Outcomes of Class X Students of SMKS Muhammadiyah Sidrap - Agussalim Agussalim; Husain Hamka; Febriani Febriani; Handy Ferdiansyah; Zulkifli N (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the effect of Cake application on English learning outcomes of class X SMKS Muhammadiyah Sidrap. This research was conducted at SMKS Muhammadiyah Sidrap in July 2021. This research is a quantitative study using the True Experimental Design method. The population in this study were students of class X SMKS Muhammadiyah Sidrap. The class was divided into 2 groups, namely the control group with 14 students and the experimental group with 15 students. Each research group uses a different learning method. The control group learns using the lecture method, while the experimental group learns using the Cake application. Data collection techniques in this study were in the form of multiple choice tests. The data analysis technique is in the form of t-test. The result of this study is that the experimental group is larger than the control group, so it can be concluded that H0 is rejected and Ha is accepted.